Kristeva’s Openness Of Text And The Issue Of Context - Attia Youcef; Mizab Manel (جامعة الوادي - University of Eloued, 2025)
When we invoke the Tel Quel group, we are immediately reminded of Julia Kristeva's contributions to critique. Such initiatives facilitated the transition from structuralist to poststructuralist assumptions, particularly through questioning the concept of closure. These modifications resulted in the creation of new categories (text productivity, text as ideologeme, phenotext, and genotext) as tools for explaining the text's openness while retaining the category of nothing out of the text. Therefore, a paradox emerges underlying the legitimacy of this problematic question: How can the relationship between the text's openness and nothing outside of text notion be justified? In other words, how did Kristeva link the text to history, society, and the subject without abandoning the premise of nothing outside the text? حين نستحضر جماعة تال كيل Tel Quel تسترعي انتباهنا جهود جوليا كريستيفا النقدية، التي أهّلت للانتقال من الطروحات البنيوية إلى الفرضيات ما بعد البنيوية، خاصة من خلال مساءلة مقولة الانغلاق، مما أسفر عن مقولات لعل أهمها: الإنتاجية النصية والنص كإيديولوجيم والنص الظاهر والنص المولد، وكل ذلك في سياق تبرير مقولة انفتاح النص، ولكن دون التخلي عن مقولة: لا شيء خارج النص. ولذلك تبرز مفارقة تبرّر شرعية السؤال الإشكالي التالي: كيف يمكن تسويغ العلاقة بين مقولة انفتاح النص ومقولة لا شيء خارج النص؟ أي كيف ربطت كريستيفا النص بالتاريخ والمجتمع والفاعل دون التخلي عن فرضية لا شيء خارج النص؟
Article .Journal of Arabic Language Sciences and Literature Vol. 17. N. 02
Keywords: Kristeva; text’s productivity; ideologeme; phenotext; genotext; كريستيفا; الإنتاجية النصية; الإيديولوجيم; النص الظاهر; النص المولد